2022
DOI: 10.1101/2022.03.07.22271999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine Learning for Real-Time Aggregated Prediction of Hospital Admission for Emergency Patients

Abstract: Machine learning for hospital operations is under-studied. We present a prediction pipeline that uses live electronic health-records for patients in a UK teaching hospital emergency department (ED) to generate short-term, probabilistic forecasts of emergency admissions. A set of XGBoost classifiers applied to 109,465 ED visits yielded AUROCs from 0.82 to 0.90 depending on elapsed visit-time at the point of prediction. Patient-level probabilities of admission were aggregated to forecast the number of admissions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted [19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted [19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted [19][20][21][22] . Like the Transparent reporting of a multivariable prediction model for individual prognosis or diagnosis (TRIPOD) or The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for reporting machine learning results 23,24 , there should be a guideline for the standardization of user interfaces (UIs) and a format for clinical decision support for end-users, including clinicians and patients.…”
Section: Discussionmentioning
confidence: 99%
“…인공지능기법을 보건의료에 적용한 연구에서는 응급실이나 중환자실의 환자 [9,10], 재원일수 [11,12], 재입원 [13,14], 진료비 [2] 등을 예측한 사례가 있다. 환자 수 예측에는 병원의 외래환자 수 예측을 위한 시계열 데이터처리 딥러닝 시스템 [10], 기계 적 학습방법을 이용한 응급실 환자 수 [9]가 있으며, 병원의 입원 재원기간 예측에 관한 연구들도 다수 존재한다 [15,16].…”
unclassified